(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
The study introduces an AI based IT governance framework, based on the data quality measurement raises, and through machine learning technology attempts to improve information system performance. The framework employs automatic pre-processing, anomaly detection and remediation as well as predictive modeling to address ITSM data issues including priority misclassification and handling time inconsistencies. The framework is applied to a real-world dataset of 46,606 incident records to present its capability of providing sound data and valuable governance insights which was validated based on cross-validated models using machine learning approach. The research delivers an open, reproducible method that supports ITSM intelligence and decision making.